Garlic (Allium sativum L.) yield and quality as affected by different integrated fertilizer levels in Wachemo University, southern Ethiopia - Abrham Shumbulo; Mihret Jemal; Abraham Bosha (PLoS ONE, 2026)
Production and productivity of garlic was constrained by many factors, among which soil fertility gradation and lack area specific fertilizer recommendation are the most important in Ethiopia. Thus, on site trial was executed at Wachemo University Lembuda demonstration field during 2021/2022 with the aims to identify the effects of NPS fertilizer and chicken manure levels on growth, bulb yield and quality and to determine the economically feasible combination of NPS and chicken manure rate for garlic productivity in the area. The treatments included four levels of chicken manure (0, 5, 10 and 15 t/ha) and five levels of NPS fertilizer (0, 50,100, 150 and 200 kg/ha) arranged factorially using a randomized complete block design (RCBD) and replicated three times. Growth, bulb yield and quality data were collected and subjected to analysis using SAS version 9.4. With the exception of days to maturity, leaf number and non-marketable bulb yield in the case of chicken manure, the majority of the investigated parameters were significantly (P < 0.05) affected by the main effects of chicken manure and NPS fertilizer. The interaction impact was not significant for nearly all of the examined variables except marketable and total bulb yield. As a result, combined application of 15 t/ha chicken manure with 150 kg/ha NPS fertilizer produced the maximum marketable bulb (19.52 t/ha) and total bulb yield (20.27 t/ha), with a 927% yield advantage over plants receiving no fertilizer. Plots with 15 t/ha chicken manure had the highest bulb dry matter (35.31%) and TSS (22.47° Brix). In terms of economic analysis, the plot treated with plants 15 t/ha of chicken manure and 150 kg/ha of NPS fertilizer had the highest net benefit (524224.8 ETB/ha) with an MRR of 10,159.1%. Hence, this combination was found to be the best and cost-effective one for smallholder farmers in the study area that could be recommended to boost garlic production and productivity.